Sodium acetate/sodium butyrate alleviates lipopolysaccharide-induced diarrhea in mice via regulating the gut microbiota, inflammatory cytokines, antioxidant levels, and NLRP3/Caspase-1 signaling - Chen, Xiushuang; Kong, Qinghui; Zhao, Xiaoxiao; Zhao, Chenxi; Hao, Pin; Irshad, Irfan; Lei, Hongjun; Kulyar, Muhammad Fakhar-e-Alam; Bhutta, Zeeshan Ahmad; Ashfaq, Hassan; Sha, Qiang; Li, Kun; et al. (Frontiers in Microbiology, 2022)
Diarrhea is a word-widely severe disease coupled with gastrointestinal dysfunction, especially in cattle causing huge economic losses. However, the effects of currently implemented measures are still not enough to prevent diarrhea. Previously we found that dropped short-chain fatty acids in diarrhea yaks, and butyrate is commonly known to be related to the epithelial barrier function and intestinal inflammation. However, it is still unknown whether sodium acetate/sodium butyrate could alleviate diarrhea in animals. The present study is carried out to explore the potential effects of sodium acetate/sodium butyrate on lipopolysaccharide-induced diarrhea in mice. Fifty ICR mice were randomly divided into control (C), LPS-induced (L), and sodium acetate/sodium butyrate (D, B, A)-treated groups. Serum and intestine samples were collected to examine inflammatory cytokines, antioxidant levels, relative gene expressions via real-time PCR assay, and gut microbiota changes through high-throughput sequencing. Results indicated that LPS decreased the villus height (p < 0.0001), increased the crypt depth (p < 0.05), and lowered the villus height to crypt depth ratio (p < 0.0001), while sodium acetate/sodium butyrate supplementation caused a significant increase in the villus height (p < 0.001), decrease in the crypt depth (p < 0.01), and increase in the villus height to crypt depth ratio (p < 0.001), especially. In mice treated with LPS, it was found that the serum level of IL-1β, TNF-α (p < 0.001), and MDA (p < 0.01) was significantly higher; however, sodium acetate/sodium butyrate supplementation significantly reduced IL-1β (p < 0.001), TNF-α (p < 0.01), and MDA (p < 0.01), respectively. A total of 19 genera were detected among mouse groups; LPS challenge decreased the abundance of Lactobacillus, unidentified F16, unidentified_S24-7, Adlercreutzia, Ruminococcus, unclassified Pseudomonadales, [Ruminococcus], Acetobacter, cc 1, Rhodococcus, unclassified Comamonadaceae, Faecalibacterium, and Cupriavidus, while increased Shigella, Rhodococcus, unclassified Comamonadaceae, and unclassified Pseudomonadales in group L. Interestingly, sodium acetate/sodium butyrate supplementation increased Lactobacillus, unidentified F16, Adlercreutzia, Ruminococcus, [Ruminococcus], unidentified F16, cc 115, Acetobacter, Faecalibacterium, and Cupriavidus, while decreased Shigella, unclassified Enterobacteriaceae, unclassified Pseudomonadales, Rhodococcus, and unclassified Comamonadaceae. LPS treatment upregulated the expressions of ZO-1 (p < 0.01) and NLRP3 (p < 0.0001) genes in mice; however, sodium acetate/sodium butyrate solution supplementation downregulated the expressions of ZO-1 (p < 0.05) and NLRP3 (p < 0.05) genes in treated mice. Also, the LPS challenge clearly downregulated the expression of Occludin (p < 0.001), Claudin (p < 0.0001), and Caspase-1 (p < 0.0001) genes, while sodium acetate/sodium butyrate solution supplementation upregulated those gene expressions in treated groups. The present study revealed that sodium acetate/sodium butyrate supplementation alleviated LPS-induced diarrhea in mice via enriching beneficial bacterium and decreasing pathogens, which could regulate oxidative damages and inflammatory responses via NLRP3/Caspase-1 signaling. The current results may give insights into the prevention and treatment of diarrhea.